Any Long-term Effect of the Beirut Port Explosion on the Airborne Particulate Matter? - Yi-Bo Zhao; Nathalie Hayeck; Najat A. Saliba; Claudia Schreiner; Markus Zennegg; Fuze Jiang; Renato Figi; Davide Bleiner; Jing Wang (Aerosol and Air Quality Research)
Abstract The Beirut port explosion in 2020 released a huge amount of chemicals including ammonium nitrate, however, the long-term effects of the explosion on air quality and public health remain unclear. In this study, particulate matter (PM10) samples were collected in Beirut, Lebanon 1 month and 3 months after the explosion. The average concentrations of main anions measured in 2020 (one and three months after the explosion) were compared with those in 2009–2015 by calculating the percentage of difference, and the average concentrations of cations and anions in September (one month after the explosion) and November (three months after the explosion) 2020 were also compared to identify any abnormal values, indicating insignificant effects on the post-explosion PM in terms of component concentrations. That is, PM and gases directly induced by the explosion might be subject to rapid atmospheric transport and deposition. Hence, the results imply that investigations of the chemical contaminations in soil and water are urgently needed. Long-term monitoring is necessary to avoid subsequent air pollution caused by possible particle resuspension. The continuous demolition and reconstruction after the explosion are possibly the main long-term effect of the Beirut port explosion, causing an elevated concentration of PM2.5 at ground level 400% higher than the recommended concentrations (15 µg m−3 for 24-hour mean). Protective measures must be taken to reduce the exposure risks by controlling the PM release from demolition and construction, traffic, and diesel generators. The cancer risk in Beirut based on PAHs measurements in 2021 was also estimated and discussed.